Positive and Negative Face on Alvin Adam’s Utterances on Just Alvin Talk Show - Agustina Lestary (STKIP PGRI Banjarmasin, 2017)
Talkshow combines entertainment and information at once and it offers more than just a monotonus story. Host has important role in a talkshow. Thus it is essential for the host to apply certain strategies when they are interviewing the guests. Alvin Adam has interviewed many public figures – from celebrities to paranormal in his Sunday night program called Just Alvin. In this paper, the writer takes the episode of Miss No Comment of Just Alvin. The guest of this show is one of Alvin’s close friends Desi Ratnasari. The writer identifies several postivie politeness strategies applied by Alvin during the programe. Alvin will use positive face strategies to give express his solidarity to Desi as he is also part of Desi’s life and will use negative face strategies to show that he knows nothing about Desi’s life